OPTIMALISASI TUGAS PERKEMBANGAN KELUARGA DENGAN ANAK USIA SEKOLAH DALAM MENCIPTAKAN GENERASI TERBAIK BANGSA - Irwina Angelia Silvanasari (LPPM Universitas dr. Soebandi, 2026)
As families develop, they go through stages, each with its own developmental tasks. Unfortunately, most families do not fully understand or even apply these family developmental tasks. The purpose of this activity is to provide an understanding of how to optimize family developmental tasks in creating the nation's best generation. The method used in this activity is divided into several sessions: problem identification, material delivery, discussion and Q&A, evaluation, conclusions, and closing. The target group is parents or families with school-age children. The presenters provide education on the stages of family development, family developmental tasks, and strategies for optimally implementing family developmental tasks. The results of this activity showed an increased understanding of the material presented. Families should be able to implement family developmental tasks according to their family stage to achieve more optimal results in supporting child growth and development